A finite-difference method for the numerical simulation of seismic wave propagation through multiscale media - Kostin, V.I.; Tcheverda, V.A.; Reshetova, G.V.; Lisitsa, V.V. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2011)
In order to simulate the interaction of seismic waves with cavernous-fractured reservoirs, a finite-difference method based on locally refined time-space grids is used. The need to use these grids is due primarily to a different scale of heterogeneities in the surrounding medium and the reservoir. The domain decomposition methods allow one to separate the target area into subdomains containing the surrounding medium (a coarse grid) and the reservoir (a fine grid). Computations for each subdomain can be carried out in parallel. The data exchange between each subdomain within a group is done using MPI through nonblocking iSend/iReceive commands. The data exchange between the two groups is done simultaneously by coupling the coarse and fine grids. Some results of the numerical simulation of a carbonate reservoir are presented and discussed.